ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA BALIKPAPAN (Studi Pada Kantor Dinas Pendapatan Daerah Kota Balikpapan - Yerni Pareang; Yudea Yudea (Jurnal Ekonomi Dan Bisnis, 2017)
Balikpapan city was given the opportunity to explore the potential of financial resources by setting taxes and fees for the region to increase revenues generated local revenues. This study aims toanalyze the contribution of local taxes and levies on revenue Balikpapan City during the last five years (2010-2014). The object of this research is the area of Balikpapan, the focus of research to address locally generated revenue, local taxes and levies. This type of research in this study is quantitative descriptive. This analysis uses the analysis of tax and levy contribution to total revenue every year. Results of this study found that the average contribution of local taxes and levies when the reception local revenues generated Balikpapan City during 2010-2014 were highly variable. The percentage contribution of local taxes is greater than the percentage contribution levies. This study contributes to the government Balikpapan to better see the potential of the region to add value to the contribution of local taxes and levies in improving revenue performance.Keywords: local taxes, levies, locally-generated revenue, Balikpapan city.